Dispensasi Perkawinan Dan Kebijakan Politik Hukum Di Indonesia - Miftakur Rohman (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2023)
The legal politics of marriage dispensation in Indonesia are related to legal policies related to the Marriage Law. Marriage dispensation is regulated in the Law due to the limitation of the minimum age for marriage which was changed to 19 years for both sexes. The legal policy of marital dispensation is influenced by philosophical and sociological considerations such as justice, benefit, expediency, and legal certainty. PERMA Number 5 of 2019 provides guidelines and standards for judges in considering and determining marriage dispensations and paying attention to the best interests of children. However, clearer clarification is needed from the State regarding emergency situations that allow for dispensation of marriage and stricter procedures for dispensing marriage to prevent early marriage.